Measuring and capturing forest values issues for the decision-maker - Gregersen, Hans; Lundren, A.; Kengen, S.; Byron, R.N. (World Forestry Congress Organizing Committee, 1997)
Important benefits are derived from forests. Decisions regarding production of forest benefits generally are made locally, or at most nationally (by national governments). Yet, many of the benefits are global and lie outside the context of local or national decisions. They are what economists call “externalities” for the decision-makers. The issues related to capturing forest values, or “internalizing the externalities” are discussed. In a political context, the question of “capture”, or who pays and who gains, arises: What mechanisms can be developed to ensure that decision-makers capture the value of the positive externalities and are made to pay for the negative ones they create? If this does not happen, then it is unlikely that they will consider them in decisions. A summary is provided of how the various forest values can be estimated and assessed. The final part of the paper discusses the question of presentation of forest value information to decision-makers, with a particular focus on the issues surrounding development of a useful and effective environmental accounting system for forests.